Social Marketing Campaign: Upaya Meningkatkan Pemahaman dan Kepatuhan Milenial Terhadap Protokol Kesehatan. DKI Jakarta - Virgo Simamora; Novi Theresia Kiak; Maria Prudensiana Leda Muga (LPMP Imperium, 2021)
Two years after the first case was detected, Indonesia is still dealing with the spread of COVID-19. Because of a lack of individual compliance to health protocols, it is becoming increasingly difficult to control. Individual compliance is influenced by several factors, the most common of which is a lack of knowledge about health protocol. This program aims to enhance millennials' knowledge of COVID-19 and encourage them to comply with the health protocol. This program was attended by 44 millennials from RT.11/RW.6, Sunter Agung, Tanjung Priok, North Jakarta, DKI Jakarta, the province with the highest number of COVID-19 cases in Indonesia. Millennials were selected because they are more likely to have asymptomatic COVID-19. This virtual training includes sharing sessions, questions and answers, and role-playing. To evaluate the difference in personal knowledge before and after the training, all participants must complete the health protocol questionnaire, previously distributed via a Google form, before and after the training. Following the training, millennial knowledge and compliance rose, according to the evaluation.